2001
DOI: 10.3141/1780-05
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment as Determinant of Walking Behavior: Analyzing Nonwork Pedestrian Travel in Portland, Oregon

Abstract: Much has been written about the connection between land use/urban form and transportation from the perspective of impacting automobile trip generation. This only addresses half the issue. The theoretical advances in land use/transportation relationships embodied in paradigms such as the jobs housing balance, Neo-Traditional Design (NTD) standards and Transit Oriented Development (TOD) rely very heavily on the generation of pedestrian traffic in order to realize their proposed benefits. The analysis presented h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(167 citation statements)
references
References 8 publications
4
156
2
5
Order By: Relevance
“…For urban transit systems (as opposed to, say, suburban systems like commuter rail), the walking catchment area tends to be particularly important, since walking is typically the primary access/egress mode for urban stations (e.g., Hsiao, et al, 1997). As a continuously growing base of research consistently reveals associations between walking behavior and the built environment (Ewing & Cervero, 2001;Greenwald & Boarnet, 2001;Guo, et al, 2007;Handy, et al, 2006), we would thus intuitively expect the built environment to exert some influence on a transit station's walk-based catchment area. Note: √ refers to significant factors; × refers to not significant factors; V.O.…”
Section: Backdrop: the Transit Station Catchment Area And The Role Ofmentioning
confidence: 99%
“…For urban transit systems (as opposed to, say, suburban systems like commuter rail), the walking catchment area tends to be particularly important, since walking is typically the primary access/egress mode for urban stations (e.g., Hsiao, et al, 1997). As a continuously growing base of research consistently reveals associations between walking behavior and the built environment (Ewing & Cervero, 2001;Greenwald & Boarnet, 2001;Guo, et al, 2007;Handy, et al, 2006), we would thus intuitively expect the built environment to exert some influence on a transit station's walk-based catchment area. Note: √ refers to significant factors; × refers to not significant factors; V.O.…”
Section: Backdrop: the Transit Station Catchment Area And The Role Ofmentioning
confidence: 99%
“…Studies that have analysed cross sectional data have incorporated a range of methods such as an instrumental variables model (Boarnet and Sarmiento, 1998;Greenwald and Boarnet, 2001;Khattak and Rodriguez, 2005;Vance and Hedel, 2007), a joint choice model (Bhat and Guo, 2007;Cervero and Duncan, 2008;Pinjari et al, 2007), a cross-sectional structural equation model (SEM) (Bagley and Mokhtarian, 2002), and a path choice model (Guo, 2009). In contrast, for a longitudinal analysis, data are collected from the same person over two or more time periods, and it is assumed that self-selection effects are nullified.…”
Section: Transit Oriented Development (Tod)mentioning
confidence: 99%
“…Furthermore, a growing number of studies have shown that there are statistically significant associations between built environment characteristics (e.g., development density, land use diversity, and street connectivity) and walking activity; specifically, mixed land use and development density are significant variables for walking activity (Ewing and Cervero, 2010;Frank et al 2006;Grasser et al, 2013;Greenwald and Boarnet, 2002;Sung et al, 2014). This study builds upon previous literature estimating impacts of built environments on pedestrian walking.…”
Section: Literature Reviewmentioning
confidence: 82%